The Role of Intermediaries in Sociotechnical Transitions: A Systematic Framework Towards Sustainability Management - Rodrigo~ Cortopassi~Goron Lobo; Marivanda~ Bortoloso Pigatto; Danielle Denes; Andrew~Jay Isaak (Business Strategy and the Environment, 2025)
Modern society grapples with socio-environmental challenges such as pandemics, climate change, resource depletion, and poverty alleviation. Recent research underscores the crucial role of intermediaries in expediting the shift towards sustainability management. This study examines how intermediaries influence sociotechnical transitions towards sustainability within the biogas technological innovation system (TIS) in Paraná state, Brazil. The relationships between transitions and entrepreneurial innovation, strategy, and ESG were examined in-depth in 27 interviews and then triangulated with historical records, using the case of the International Center of Renewable Energies and Biogas (CIbiogás)—an organization created with the support of the United Nations. Findings indicate that intermediaries are pivotal in facilitating sociotechnical transitions through connections with individuals, networks, and organizations. The paper contributes to the literature on sociotechnical transitions by deepening our understanding of intermediaries' role in transitions towards sustainability and by furnishing a systematic framework to guide future research in this domain.
Keywords: Q01; Q56; Q55; L14; O31; O33; 650; Sustainability Management; Sociotechnical Transitions; Energy Industry; Emerging Market; Case Study; Technological Innovation System; Qualitative Research